Dynamic simulation and key influencing factors of carbon storage in the water-depleted zones of an arid Inland River Basin: Insights from the Tarim River mainstream - Kun Liu; Bin Wu; Fan Gao; Yunfei Chen; Bing He; Abdul Waheed; Aishajiang Aili; Zhiyuan Xu; Fanghong Han; Hailiang Xu (Ecological Informatics)
Arid inland river basins exhibit pronounced uncertainty and spatial heterogeneity in carbon storage dynamics due to extreme climate conditions, water scarcity and ecosystem vulnerability. In particular, water-depleted zones still lack systematic research on the evolution mechanism of carbon storage. To assess the evolution characteristics of carbon storage in such regions, this study developed an integrated framework combining the Patch-generating Land Use Simulation (PLUS) model, the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model and a Structural Equation Model (SEM), taking the Tarim River mainstream as a representative case. It systematically analyzed the spatial and temporal evolution of land use/cover change (LUCC) and carbon storage from 1990 to 2020, simulated future trends under three scenarios: natural development (ND), cultivated land protection (CP) and ecological protection (EP), covering from 2030 to 2050, and quantitatively identified the direct and indirect drivers of spatial differentiation in carbon storage. The results revealed that over the past three decades, the most significant land transitions in the Tarim River mainstream occurred in cultivated and build-up land. Among the three scenarios, within the EP scenario, the reduction in carbon storage by 2030, 2040, and 2050 was significantly alleviated, with an additional 56 × 105 tons of carbon stored compared to the cultivated land protection scenario. LUCC emerged as the dominant directly driver of regional carbon storage changes. Additionally, carbon storage in the upper, middle, and lower reaches was indirectly influenced by socio-economic and natural geographical factors, with the dominant factor varying by region. These differences modified water resource supply patterns, influenced vegetation dynamics, and ultimately indirectly affected the spatial and temporal evolution of carbon storage. This study enriches the understanding of carbon storage evolution mechanisms in arid regions and underscores the importance of region-specific carbon management strategies tailored to local conditions.